Legal Engineering Towards Fulfillment of The Requirements Prospective Heirs from Perspective of Islamic Inheritance Law - Sularno, Sularno (International Journal on Advanced Science, Education, and Religion, 2025)
This article discusses legal engineering in the context of fulfilling the requirements for someone to become an heir according to Islamic inheritance law. In practice, there are certain conditions in which someone does not immediately meet the requirements as an heir due to various reasons, such as differences in religion, criminal acts against the heir, or a marital status that is not yet valid under Islamic law. Through a juridical-normative approach and literature study, this article explores the possibility of legal engineering within the limits of the sharia corridor to accommodate the needs of justice and welfare in the family. This study shows that legal engineering in the form of contemporary ijtihad, reinterpretation of nas, and utilization of positive law can be a solution to formal obstacles that hinder someone from obtaining inheritance rights. However, its application must still be based on the principles of justice, welfare, and not conflict with the basic values of Islamic law. This article is expected to contribute to the development of Islamic family law, especially in the field of inheritance.